2022
DOI: 10.3389/fnut.2022.929210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Green Teas on Obesity and Non-Alcoholic Fatty Liver Disease Induced by a High-Fat Diet in Mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) and obesity are serious public health problems. Green tea is widely consumed in the world and different green teas could possess different bioactivities. In this study, the effects of 10 selected green teas on obesity and NAFLD were evaluated and compared. The mice fed with a high-fat diet were intervened with green tea extract (200 mg/kg body weight) for 15 weeks. Most of these teas were first evaluated for their effects on obesity and NAFLD. The results showed that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Several recent reports have given similar findings (Wu et al, 2021; D.‐D. Zhou, Mao, et al, 2022), but interestingly, EGCG was shown to ameliorate NAFLD/NASH by modulating intestinal immunity and macrophage polarization (Du et al, 2021; Huang et al, 2020).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 58%
See 1 more Smart Citation
“…Several recent reports have given similar findings (Wu et al, 2021; D.‐D. Zhou, Mao, et al, 2022), but interestingly, EGCG was shown to ameliorate NAFLD/NASH by modulating intestinal immunity and macrophage polarization (Du et al, 2021; Huang et al, 2020).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 58%
“…In addition, Li and colleagues revealed that EGCG suppressed hepatic cholesterol synthesis through activation of the SIRT1/FOXO1 signaling pathway, consequently ameliorating dyslipidemia in rats (Li & Wu, 2018). Several recent reports have given similar findings (Wu et al, 2021;D.-D. Zhou, Mao, et al, 2022), but interestingly, EGCG was shown to ameliorate NAFLD/NASH by modulating intestinal immunity and macrophage polarization (Du et al, 2021;Huang et al, 2020).…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 86%
“…Obesity can be prevented by regular physical activity, balanced nutrition, and the consumption of healthy foods. A number of studies have provided evidence for obesity-preventing foods, which are mostly plant-based and include garlic (Kagawa et al, 2020), ginger (Seo et al, 2021), tea (Zhou et al, 2022), and edible sprouts (Kim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an emerging purple tea variety derived from the same tea plant is now commercially produced as a healthy beverage. In general, tea—especially green tea—is considered a healthy beverage due to its high content of polyphenols which have demonstrated potential positive health effects via their roles as antioxidants [ 2 , 3 , 4 , 5 , 6 ], immune stimulators and anti-cancer [ 7 ], anti-obesity and anti-diabetic [ 8 , 9 , 10 ], anti-alcoholism [ 11 ], anti-hypertension [ 12 ] and anticardiovascular [ 13 ] diseases. The composition of polyphenols varies among teas and is influenced by a number of factors including tea variety, growing environment and processing method [ 14 ].…”
Section: Introductionmentioning
confidence: 99%